Ressonância Magnética Nuclear na análise de suco de laranja: importantes aplicações - Maia, Giovanna (Universidade Federal de São Carlos, 2025)
The Nuclear Magnetic Resonance (NMR) technique has emerged as a powerful analytical tool in the food industry, especially in the characterization of natural juices, such as orange juice. This technique allows for fast, accurate, and non-destructive analyses, with the ability to provide detailed information on the chemical composition and metabolic profile of samples. This study aimed to survey the literature on the fundamentals of NMR and its application in the analysis of orange juice, focusing on the identification of sugars, flavonoids, and bioactive compounds. In addition, the use of NMR in the differentiation of samples based on geographic origin was explored through the analysis of specific metabolic profiles. The implications of this technique for quality control and verification of product authenticity were also discussed, since variations in chemical composition may indicate adulteration or changes in the production process. Through univariate and multivariate analyses of the obtained spectra, it was possible to develop robust models for origin discrimination, quantification of constituents and fraud detection, contributing significantly to traceability and standardization in the orange juice production chain.
Nuclear Magnetic Resonance on orange juice analysis: important applications
Keywords: Ressonância magnética nuclear; Suco de laranja; Perfil metabólico; Controle de qualidade; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::ESTRUTURA, CONFORMACAO E ESTEREOQUIMICA